Spontaneous Cervical Intradural Disc Herniation Associated with Ossification of Posterior Longitudinal Ligament - Dachuan Wang; Haifeng Wang; Wun-Jer Shen (Case Reports in Orthopedics)
Intradural herniation of a cervical disc is rare; less than 35 cases have been reported to date. A 52-year-old man with preexisting ossification of posterior longitudinal ligament developed severe neck pain with Lt hemiparesis while asleep. Neurological exam was consistent with Brown-Séquard syndrome. Magnetic resonance images showed a C5-6 herniated disc that was adjacent to the ossified ligament and indenting the cord. The mass was surrounded by cerebrospinal fluid signal intensity margin, and caudally the ventral dura line appears divided into two, consistent with the “Y-sign” described by Sasaji et al. Cord edema were noted. Because of preexisting canal stenosis and spinal cord at risk, a laminoplasty was performed, followed by an anterior C6 corpectomy. Spot-weld type adhesions of the posterior longitudinal ligament to the dura was noted, along with a longitudinal tear in the dura. An intradural extra-arachnoid fragment of herniated disc was removed. Clinical exam at 6 months after surgery revealed normal muscle strength but persistent mild paresthesias. It is difficult to make a definite diagnosis of intradural herniation preoperatively; however, the clinical findings and radiographic signs mentioned above are suggestive and should alert the surgeon to look for an intradural fragment.